Literasi Numerasi Siswa Sanggar Belajar Sungai Mulia Kuala Lumpur Dalam Pembelajaran Holistic - Minsih, Minsih; Utami, Ratnasari Diah; Wulandari, Murfiah Dewi; Hidayati, Cahya; Raisia, Aliifah (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2024)
The purpose of this service is to provide teachers and facilitators with an understanding of holistic learning so that they are able to apply it in learning, provide assistance in the implementation of holistic learning in improving the literacy and numeracy abilities of students in the Sungai Mulia 5 Learning Studio, Kuala Lumpur. Assistance in strengthening literacy and numeracy through holistic learning. By providing this reinforcement, it is hoped that students at the Indonesian Learning Center under the coordination of the Kuala Lumpur Indonesia School in Kuala Lumpur Malaysia will have a good understanding of knowledge in aspects of literacy and numeracy. This service method goes through five stages, (1) Mapping the initial conditions of partner learning studios, (2) Socialization is carried out to discuss with partners regarding the implementation of community service, (3) Training and assistance to students regarding literacy and numeracy through holistic learning, (4) Monitoring and evaluation of the abilities of students in the Mulia 5 river learning studio, and (5) preparation of reports, follow-up and recommendations as well as publication in the form of articles. The results of this community service activity show that the application of literacy and numeracy with holistic learning has become more organized and resulted in increased literacy and numeracy skills, this is after the overall test was carried out for more than a month the facilitators implemented holistic learning in the Sungai SB Start 5.